Short term outcome of open reduction and internal fixation with plating in displaced intra articular calcaneal fractures - Thakur, Amit; Lone, Zubair A.; Mohd, John; Darokhan, Mohammad Azhar ud din; Ali, Tanveer; Arfee, Sakib (International Journal of Research in Medical Sciences, 2020)
Background: Calcaneum fractures constitute the majority of the tarsal bone fractures worldwide. There is no gold standard consensus as of now for the management of the displaced intra articular calcaneal fractures. Open reduction and internal fixation with plating is one of the management options available. Methods: Authors studied the results of open reduction and internal fixation with plating in 22 calcaneal fractures in a study with a minimum follow up of 6 months. Outcome was studied using Maryland foot score. Results: Authors observed excellent results in 5 patients (22.72%), good results in 12 patients (54.54%), fair results in 4 patients (18.18%) and poor result in 1 patient (04.54%). Authors encountered wound infection in 1 patient (4.54%), heel varus in 1 patient (4.54%), heel broadening in 1 patient (4.54%), reduced range of motion at ankle in 2 patients (9.9%) and persistent heel pain in 1 patient (4.54%). Conclusions: Open Reduction and Internal Fixation (ORIF) with calcaneum plating, through an extensive lateral approach, for displaced intra articular fractures of the calcaneum is an effective treatment modality with very good results in experienced hands.